2011
DOI: 10.5152/akd.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluoroscopy time during coronary angiography and interventions by radial and femoral routes- can we decrease the fluoroscopy time with increased experience? An observational study

Abstract: Comparison of fluoroscopy time during coronary angiography and interventions by radial and femoral routes-can we decrease the fluoroscopy time with increased experience? An observational study Radiyal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
(28 reference statements)
5
16
1
Order By: Relevance
“…Many authors believe that the fluoroscopy time, an indirect measure of the difficulty of the procedure, is greater in PCI through radial access than through femoral access. The present results were consistent with those described by Farman et al 9 for PCI through radial access, and shorter than that demonstrated by Alli et al 10 for femoral access. It is important to mention that the surgeons must be familiar with the technique in order to achieve angiographic success and a low crossover rate of the access route in order to avoid delay of coronary reperfusion.…”
Section: Discussionsupporting
confidence: 83%
“…Many authors believe that the fluoroscopy time, an indirect measure of the difficulty of the procedure, is greater in PCI through radial access than through femoral access. The present results were consistent with those described by Farman et al 9 for PCI through radial access, and shorter than that demonstrated by Alli et al 10 for femoral access. It is important to mention that the surgeons must be familiar with the technique in order to achieve angiographic success and a low crossover rate of the access route in order to avoid delay of coronary reperfusion.…”
Section: Discussionsupporting
confidence: 83%
“…One observational cohort study evaluated 928 patients who underwent diagnostic coronary angiograms via TFA (n = 734) or TRA (n = 194) and demonstrated FT to be 58% higher in the TRA compared with TFA group. 13 They repeated the analysis with a subgroup of experienced TRA operators and showed FT to be 29% higher in the TRA compared with TFA group. Our results are consistent with this study showing increased FT and radiation exposure with TRA even with experienced operators.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attempted to determine whether or not there is a difference in patient radiation exposure for coronary angiography and percutaneous coronary intervention (PCI) depending on the arterial access route. The results of these studies have varied, with most studies finding measures of radiation exposure to be higher with radial access [2,4,7,8,9,10,11,12,13,14], some showing no appreciable difference between access routes [15,16,17] and one study finding higher exposure with femoral compared to radial access [18]. Differences in the results of these studies may be attributed to many study design and patient factors, including study methodology, different measures of radiation exposure, patient demographics and variability in included procedures.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%